FAKTOR-FAKTOR PENENTU STRUKTUR MODAL DAN PENGARUHNYA TERHADAP NILAI PERUSAHAAN - Faisal Riza Rahman, 14.05.51.0284; Taswan, Taswan (Students' Journal of Economic and Management, 2018)
This study aims to test and analyze the effect of dividend policy, liquidity, profitability, and firm size on capital structure. This research also examines the influence of capital structure on the value of listed companies in IDX period 2012-2016. The data used are Indonesia Capital Market Directory 2015 and Financial Report as of December 31, 2016 that are sampled. Sampling method uses purposive sampling method with 33 companies listed in IDX. Data types used are secondary data which is panel data, because it is a combination of time series and cross section data. The analysis method used is fixed effect model estimation method and random effect model. The selection of estimation method was based on hausman test. The result of research showed that DPR, CR, ROE, and SIZE had a negative effect on DER. DPR and SIZE variables have no significant effect while CR and ROE are significant. DER has a negative effect not significantly on PBV. This study found no influence on capital structure of its independent variables. Keywords: Capital, Dividend Policy, Profitability, Company Value, Liquidity, Open Company and Company Size